Animal experimentation a guide to the issues - Monamy, Vaughan 1958- (Cambridge University Press, 2017)
"This fully updated third edition includes discussion of genetically altered animals and associated welfare and ethical issues that surround the breeding programmes in animal based research. The book discusses the origins of vivisection, the advances in human and non-human welfare made possible by animal experimentation, moral objections, and alternatives to the use of animals in research. It also examines the regulatory umbrella under which experiments are conducted in Europe, USA and Australasia. The author highlights the future responsibilities of researchers who will be working with animals, and offers practical advice on experimental design, literature search, consultation with colleagues, and the importance of the ongoing search for alternatives."-- Back cover.